Postoperative periodontal pain prevention using two dexamethasone medication protocols: A double-blind, parallel-group, placebo-controlled randomized clinical trial - Steffens, Joao Paulo [UNESP]; Santos, Fábio André; Pilatti, Gibson Luiz (My University, 2011)
To assess and compare the efficacy of two different dexamethasone protocols on pain prevention following periodontal surgery. Methods: 60 subjects presenting moderate to severe periodontitis with persisting clinical signs of inflammation after nonsurgical periodontal therapy on at least two adjacent teeth were scheduled for open flap debridement surgeries. This was a double-blind, parallel-group, placebo-controlled randomized clinical trial. Each patient was randomly assigned to receive one of the following preoperative medication protocols, 1 hour before surgery: Protocol 1 (Pl): 4 mg dexamethasone, and another 4 mg 8 hours after the first dose; P2: 8 mg dexamethasone; P3: placebo. Pain intensity was evaluated hourly for the first 8 hours after surgery using the visual analogue scale (VAS). For ethical reasons, patients were instructed to use acetaminophen 750 mg as a rescue medication, only in case of pain. Results: P2 demonstrated to be more effective than P3 at all time periods, except for the 2nd hour. P2 was also superior to Pl at 1(Kruskal-Wallis; P= 0.034), 5- (P= 0.03), 6- (P=0.04), 7- (P= 0.005) and 8-hour (P= 0.01) periods. The need for rescue medication was significantly prevented when P2 was used (ANOVA; P= 0.02),.